Numerical simulation of CBR test and HS-Small parameter characterization for Bogotá soils - Camilo Ernesto Herrera-Cano; Juan Carlos Ruge-Cárdenas; Juan Gabriel Bastidas-Martínez (Dyna)
This paper presents the determination of HS-Small constitutive model parameters for the Sabana Formation, the major deposit of Bogotá city. Mechanical parameters were obtained from index parameter of physical characterization, using correlations consulted as state-of-the-art. The characterization obtained has been validated with a numerical model of the CBR test, showing good agreement with typical values in the City of Bogotá. The methodology presented here would make possible the determination of the HS-Small parameters for the entire profile of the Sabana Formation. Once the parameter sets of the samples have been validated, a parametric analysis is performed, varying the friction angle and the shear module values. This parametric study shows that for the HS Small constitutive model, the stiffness modulus has a greater contribution in the CBR test than the friction angle, which would support the correlations between the resilient modulus and the CBR value; correlations widely used in pavement engineering. The methodology of characterization presented here would make possible the determination of the HS-Small parameters for the entire profile of the Sabana Formation. This allows for the numerical simulation of complex geotechnical works in the early stages of design when advanced mechanical laboratory tests are not available.